Evaluating Implementation Factors of Indigenous Communities in Northern Ontario for eConsult - Morris, Jessica Marie; Liddy, Clare (Global Health: Annual Review, 2020)
The creation of innovative platforms is of limited benefit if not implemented properly with careful consideration of regional contexts. Digital health platforms can be a tool that may improve access to quality care for residents of Northern Ontario. The health innovations framework of Chaudoir et al. [1] was used to address patient, provider, organization, and system level factors relevant to the implementation of electronic consultation (eConsult) in the North West Local Health Integration Network (LHIN) for Indigenous communities. An environmental scan was conducted through a systematic literature search of three databases and grey literature. For the implementation of eConsult in Indigenous communities in Northern Ontario, it was recommended that: (1) an Indigenous care expert should be consulted to include features that ensure the provision of culturally competent care to patients; (2) further investigation into the role of nurses and nurse practitioners in Indigenous communities should be conducted; (3) the possibility of partnering with provincial Aboriginal Health Access Centres and the Northern Ontario School of Medicine should be explored; (4) the gain of federal government funding and support; and (5) the function of eConsult should potentially extend to act as a centralized source of public health information. Extreme regional diversity is prevalent across Northern Ontario, and additional analyses should be done at a more local level prior to the implementation of eConsult.